Mythopoetic Worldview of Bunin: Linguistic and Literary and Cultural Analysis Aspects - N. A. Borodina; O. A. Selemeneva; N. A. Trubitsina (Научный диалог)
The results of the analysis of semantic groups of mythonyms of the poetic heritage of I. A. Bunin as means of explication of various historical-informational and cultural-symbolic worldview meanings are presented in the article. The relevance of the work is due to the interest of literary onomastics in identifying units of the onomastic code of artistic and aesthetic systems of various domestic and foreign writers. The novelty of the work is associated with the inclusion of lexical units with different ratios of the nominated image and denotation into the Bunin mythonymicon, with the synthesis of linguistic and literary-cultural approaches in characterizing each of the selected lexical units. The twelve described semantic groups of mythological names are organized in the form of a field with a core and peripheral parts. For each group, the features of contextual use are noted. The authors come to the conclusion that in the Bunin picture of the world, mythonyms of various semantics perform text-forming and meaning-forming functions. They not only represent archetypal images (Fire, Bottom, Feminine, Garden, etc.), axiological oppositions (light — darkness, good — evil, etc.), key ideas, themes and motives (the idea of being still, themes of love, death, motives of temptation, resurrection, dreams, etc.), historiosophical concepts (moral choice and fortitude), but also participate in the creation of an individual author’s myth.